Giant aufeis in the Pangong Tso Basin: inventory of a neglected cryospheric component in Eastern Ladakh and Western Tibet - Schmitt, Tobias; Brombierstäudl, Dagmar; Schmidt, Susanne; Nüsser, Marcus (Atmosphere, 2024)
Cryosphere studies in High Mountain Asia (HMA) typically focus on glaciers, seasonal snow cover, and permafrost. As an additional and mostly overlooked cryosphere component, aufeis occurs frequently in cold-arid regions and covers extensive areas of the Trans-Himalaya and Tibetan Plateau. This largely neglected cryosphere component generally forms in winter from repeated freezing of seepage or overflow. In this article, the occurrence of aufeis fields in the endorheic Pangong Tso Basin (PTB), with a total area of 31,000 km2, is inventoried and examined. Based on a semi-automatic remote sensing approach using Sentinel-2 imagery, about 1000 aufeis fields were detected in the spring of 2019, covering a total area of approximately 86 km2 and with an average individual size of 0.08 km2, while the largest field covered an area of 14.8 km2. A striking contrast between the northern and southern portions of the PTB characterized the spatial distribution of large aufeis fields. All large (>0.5 km2) and 13 persisting aufeis fields were located along broad valleys in the northern portion. Furthermore, a multi-temporal comparison between 1994 and 2023 shows that the number of remaining aufeis fields in autumn varied between 8 and 29, with a maximum in 2019. Their total area ranged between about 0.3 km2 in 1994 and 2023 to about 1.2 km2 in 2015 and 2019. This study complements recent aufeis inventories from the Trans-Himalayan region of Ladakh and closes the gap to the Tibetan Plateau.
Gesehen am 06.03.2024